2014
DOI: 10.3732/ajb.1400097
|View full text |Cite
|
Sign up to set email alerts
|

Transitions in photoperiodic flowering are common and involve few loci in wild sunflowers (Helianthus; Asteraceae)

Abstract: Together, these findings (1) reveal that substantial variation in the nature of flowering time responses to photoperiod cues has arisen during the evolution of wild sunflowers and (2) suggest these transitions may be largely characterized by simple genetic architectures. Thus, introgression of wild alleles may be a tractable means of genetically tailoring sunflower cultivars for climate-specific production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 83 publications
1
10
0
Order By: Relevance
“…Blackman et al 2011;Moyers & Rieseberg 2013), the patterns of genetic and phenotypic differentiation that we characterize have not been previously reported. In particular, H. argophyllus is described as 'the latest blooming of the annual sunflowers' (Heiser 1951) and as obligately flowering in response to short daylengths (Henry et al 2014). However, the early-flowering plants that we observe are likely long daylength sensitive, and largely overlap in flowering with the sympatric annual sunflowers H. annuus, H. debilis and H. praecox (B.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Blackman et al 2011;Moyers & Rieseberg 2013), the patterns of genetic and phenotypic differentiation that we characterize have not been previously reported. In particular, H. argophyllus is described as 'the latest blooming of the annual sunflowers' (Heiser 1951) and as obligately flowering in response to short daylengths (Henry et al 2014). However, the early-flowering plants that we observe are likely long daylength sensitive, and largely overlap in flowering with the sympatric annual sunflowers H. annuus, H. debilis and H. praecox (B.…”
Section: Discussionmentioning
confidence: 64%
“…In particular, H. argophyllus is described as ‘the latest blooming of the annual sunflowers’ (Heiser ) and as obligately flowering in response to short daylengths (Henry et al . ). However, the early‐flowering plants that we observe are likely long daylength sensitive, and largely overlap in flowering with the sympatric annual sunflowers H. annuus , H. debilis and H. praecox (B. Moyers, personal observation; Heiser et al .…”
Section: Discussionmentioning
confidence: 97%
“…In Helianthus, flowering is strongly influenced by both photoperiod and temperature cues (Leon et al, 2001). Days to anthesis has been noted to decrease with increasing latitude in Maximilian sunflower and other wild Helianthus species (Kawakami et al, 2011;Henry et al, 2014), and a latitudinal effect on flowering was observed in populations collected for this study of plants grown both in common garden plots and growth chambers. Single nucleotide polymorphisms associated with temperature (frost-free days, average daily June temperature, and elevation), days to anthesis, and capitulum diameters were detected.…”
Section: Environmental Associations and Implications For Selecting Fomentioning
confidence: 60%
“…Often tradeoffs are observed between biomass accumulation and timing of reproduction (Egli, 2011). Days to anthesis has been noted to decrease with increasing latitude in Maximilian sunflower and other wild Helianthus species (Kawakami et al, 2011;Henry et al, 2014), and a latitudinal effect on flowering was observed in populations collected for this study of plants grown both in common garden plots and growth chambers. In Helianthus, flowering is strongly influenced by both photoperiod and temperature cues (Leon et al, 2001).…”
Section: Environmental Associations and Implications For Selecting Fomentioning
confidence: 65%
“…Association and quantitative trait locus (QTL) mapping studies of photoperiod response have implicated anywhere from a handful to as many as 14 loci contributing to intraspecific variation (e.g. Coles et al, 2010;Anderson et al, 2011;Hung et al, 2012;Henry et al, 2014;Jiang et al, 2014). Some of these loci represent allelic series, and different subsets of the loci may be combined to produce equivalent day-neutral phenotypes (e.g.…”
Section: Variation In Magnitude Of Photoperiodic Responsementioning
confidence: 99%